The Arabidopsis Mediator Complex Subunit16 Is a Key Component of Basal Resistance against the Necrotrophic Fungal Pathogen Sclerotinia sclerotiorum . Issue 1 (4th July 2015) - Wang, Chenggang; Yao, Jin; Du, Xuezhu; Zhang, Yanping; Sun, Yijun; Rollins, Jeffrey A.; Mou, Zhonglin
Abstract : An evolutionarily conserved gene regulates resistance to a devastating necrotrophic fungal crop plant pathogen by controlling major antifungal defense pathways. Abstract: Although Sclerotinia sclerotiorum is a devastating necrotrophic fungal plant pathogen in agriculture, the virulence mechanisms utilized by S. sclerotiorum and the host defense mechanisms against this pathogen have not been fully understood. Here, we report that the Arabidopsis ( Arabidopsis thaliana ) Mediator complex subunit MED16 is a key component of basal resistance against S. sclerotiorum . Mutants of MED16 are markedly more susceptible to S. sclerotiorum than mutants of 13 other Mediator subunits, and med16 has a much stronger effect on S. sclerotiorum -induced transcriptome changes compared with med8, a mutation not altering susceptibility to S. sclerotiorum . Interestingly, med16 is also more susceptible to S. sclerotiorum than coronatine-insensitive1-1 ( coi1-1 ), which is the most susceptible mutant reported so far. Although the jasmonic acid (JA )/ethylene (ET ) defense pathway marker gene PLANT DEFENSIN1.2 ( PDF1.2 ) cannot be induced in either med16 or coi1-1, basal transcript levels of PDF1.2 in med16 are significantly lower than in coi1-1 . Furthermore, ET -induced suppression of JA -activated wound responses is compromised in med16, suggesting a role for MED16 in JA -ET cross talk. Additionally, MED16 is required for the recruitment of RNA polymerase II to PDF1.2 and OCTADECANOID-RESPONSIVE ARABIDOPSIS ETHYLENE/ETHYLENE-RESPONSIVE FACTOR59 ( ORA59 ), two target genes of both JA /ET -mediated and the transcription factor WRKY33-activated defense pathways. Finally, MED16 is physically associated with WRKY33 in yeast and in planta, and WRKY33-activated transcription of PDF1.2 and ORA59 as well as resistance to S. sclerotiorum depends on MED16. Taken together, these results indicate that MED16 regulates resistance to S. sclerotiorum by governing both JA /ET -mediated and WRKY33-activated defense signaling in Arabidopsis.